2018
DOI: 10.5578/khj.66119
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Prothrombin Time in Patients with Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention

Abstract: Introduction: There are some studies regarding the prognostic value of coagulation abnormalities both in heart failure and acute pulmonary embolism patients. However, it is unclear whether prothrombin time (PT) at presentation will be associated with long-term mortality in acute coronary syndrome (ACS) patients not on anticoagulant therapy. Thus, we investigated the prognostic role of initial PT in such patients. Patients and Methods: A total of 1100 consecutive patients with ACS undergoing percutaneous corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…Besides its well-established pro-coagulant functions (activation of platelets, fibrinogen, and other coagulation factors), thrombin, together with thrombomodulin, is also an activator of the key anti-coagulant protein C [17] which itself has direct cytoprotective effects that may slow the progression of CAD [17]. Our data are also in line with a recent publication that reported an inverse association of prothrombin time/INR with risk in patients with ACS [8] and we observe a similar association in our subgroup of patients with ACS (Figure D in S1 File).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Besides its well-established pro-coagulant functions (activation of platelets, fibrinogen, and other coagulation factors), thrombin, together with thrombomodulin, is also an activator of the key anti-coagulant protein C [17] which itself has direct cytoprotective effects that may slow the progression of CAD [17]. Our data are also in line with a recent publication that reported an inverse association of prothrombin time/INR with risk in patients with ACS [8] and we observe a similar association in our subgroup of patients with ACS (Figure D in S1 File).…”
Section: Discussionsupporting
confidence: 87%
“…Recently, the association of INR on admission with the 90-day mortality of critically ill patients who underwent endarterectomy during hospitalization has been shown [6], and also that the prothrombin time-albumin ratio (PTAR) predicted 90-day mortality in critically ill patients with liver cirrhosis [7]. Another study reported that prolonged initial prothrombin time or higher INR in the absence of anticoagulant therapy was associated with all-cause mortality in patients with acute coronary syndrome who were undergoing percutaneous coronary intervention [8] and the INR has been shown to be associated with mortality in acute pulmonary embolism [9].…”
Section: Introductionmentioning
confidence: 99%
“…ACS consisted of: UA, NSTEMI, and STEMI. The diagnosis of UA was defined in the presence of acute chest discomfort described as chest pain or chest pain equivalent symptoms (dyspnea) and ECG changes indicating myocardial ischemia: persistent or transient ST depression, T wave inversion, flat T waves, pseudonormalization of T waves, without evidence of cardiomyocyte necrosis, respectively with normal high-sensitivity cardiac troponin I value [ 10 ]. NSTEMI was diagnosed if acute chest discomfort or ECG changes indicating myocardial ischemia were associated with elevation of cardiac markers of myocardial necrosis, respectively high sensitivity troponin I [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of UA was defined in the presence of acute chest discomfort described as chest pain or chest pain equivalent symptoms (dyspnea) and ECG changes indicating myocardial ischemia: persistent or transient ST depression, T wave inversion, flat T waves, pseudonormalization of T waves, without evidence of cardiomyocyte necrosis, respectively with normal high-sensitivity cardiac troponin I value [ 10 ]. NSTEMI was diagnosed if acute chest discomfort or ECG changes indicating myocardial ischemia were associated with elevation of cardiac markers of myocardial necrosis, respectively high sensitivity troponin I [ 10 ]. STEMI was defined if acute chest discomfort was associated with persistent ST elevation in at least two contiguous leads, with an amplitude measured at J point of ≥2.5 mm in men <40 years, ≥2 mm in men ≥40 years, or ≥1.5 mm in women in leads V2-V3 and/or ≥1 mm in the other leads (in the absence of left ventricular hypertrophy or left bundle branch block) [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…37 We found that the PT, PTT, and INR levels in our investigation were comparable to the findings of prior investigations. 23,24,[38][39][40] The retrospective study performed by Kırış et al 38 reported that prolonged initial PT without anticoagulant medication use has been linked to all-cause death in patients with ACS following percutaneous coronary intervention (PCI) and PT can be used to determine ACS patients with high risk. Prothrombin time and APTT were elevated in acute MI patients receiving anticoagulants therapy in a study carried out by Saxena et al 39 and by Khan et al 40 According to the studies carried out by Babes et al 24 and Adam et al, 23 PT was useful in predicting mortality and consequences in ACS patients.…”
mentioning
confidence: 99%